Pengaruh Kompetensi Aparatur Desa, Sistem Pengendalian Internal dan Transparansi Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Empiris Pada Kecamatan Tanjung Morawa) - Tia Pratiwi; Mas'ut Mas'ut; Lusi Elviani Rangkuti; Ilham Sonata (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2026)
The purpose of this study is to analyze the effects of village apparatus competence, internal control systems, and transparency on the accountability of village fund management. This study employed a quantitative approach with a sample of 78 village officials in Tanjung Morawa District. The sampling technique used was total sampling or census method, in which the entire population was included as the research sample. Data were analyzed using multiple linear regression, including partial testing (t-test), simultaneous testing (F-test), and the coefficient of determination test. The results showed that village apparatus competence had a positive and significant effect on the accountability of village fund management. The internal control system also had a positive and significant effect on the accountability of village fund management. In addition, transparency was found to have a positive and significant effect on the accountability of village fund management. Simultaneously, these three variables contributed to improving the accountability of village fund management.